Wipeout: Sangley mercantile dominance and persistence in the Spanish colonial period in the Philippines - Raul V. Fabella (University of the Philippines, School of Economics (UPSE), 2012)
Documentary evidence of the emergence and the eventual complete dominance of the Chinese mercantile traders (Sangleys) during the Spanish colonial period in the Philippines is first presented. We identify the critical traits in the Sangley mercantile genome and the new contractual and organizational technologies which led to the wipeout of non-Sangley merchants from the market. A Malthusian replicator dynamics is proposed to explain the wipeout process. We explain the persistence of the mercantile dominance of Sangleys via the forces serving to curve abuse of market power and non-assimilation of winning Sangley traits by non-Chinese following the Akerlof-Kranton identity economics.
Keywords: N0; L10; 330; Market dominance; Sangley traits; Emergence; Ethnicity; Unternehmer; Chinesen; Marktmacht; Kolonialismus; Philippinen